Contributing to collaborative health governance in Africa : a realist evaluation of the Universal Health Coverage Partnership - (:unkn) unknown (My University, 2022)
Background Policy dialogue, a collaborative governance mechanism, has raised interest among international stakeholders. They see it as a means to strengthen health systems governance and to participate in the development of health policies that support universal health coverage. In this context, WHO has set up the Universal Health Coverage Partnership. This Partnership aims to support health ministries in establishing inclusive, participatory, and evidence-informed policy dialogue. The general purpose of our study is to understand how and in what contexts the Partnership may support policy dialogue and with what outcomes. More specifically, our study aims to answer two questions: 1) How and in what contexts may the Partnership initiate and nurture policy dialogue? 2) How do collaboration dynamics unfold within policy dialogue supported by the Partnership? Methods We conducted a multiple-case study realist evaluation based on Emerson's integrative framework for collaborative governance to investigate the role of the Partnership in policy dialogue on three policy issues in six sub-Saharan African countries: health financing (Burkina Faso and Democratic Republic of Congo), health planning (Cabo Verde, Niger, and Togo), and aid coordination for health (Liberia). We interviewed 121 key informants, analyzed policy documents, and observed policy dialogue events. Results The Partnership may facilitate the initiation of policy dialogue when: 1) stakeholders feel uncertain about health sector issues and acknowledge their interdependence in responding to such issues, and 2) policy dialogue coincides with their needs and interests. In this context, policy dialogue enables stakeholders to build a shared understanding of issues and of the need for action and encourages collective leadership. However, ministries' weak ownership of policy dialogue and stakeholders' lack of confidence in their capacity for joint action hinder their engagement and curb the institutional
Keywords: African Research